PURIFICATION AND CHARACTERIZATION OF THE NEWLY THERMOSTABLE PROTEASE PRODUCED BY Brevibacillus thermoruber LII ISOLATED FROM PADANG CERMIN HOTSPRING, INDONESIA - Zilda, Dewi Zeswita; Harmayani, Eni; Widada, Jaka; Asmara, Widya; Irianto, Hari Eko; Patantis, Gintung; Fawzya, Yusro Nuri (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2014)
Thermo stability is among of the vital enzyme characteristics for industrial application.Â Brevibacillus thermoruber LII was obtained as a potential isolate from the previous researchwhich screened the potential thermostable protease producing bacteria from Indonesian hotspring.The newly thermostable protease produced by thermophilic Brevibacillus thermoruber LII hadbeen purified and characterized. It was predicted that the pure enzyme obtained from Brevibacillusthermoruber LII was homo hexameric, having molecular weight of 36 kDa unit protein and itsnative was 215 kDa. In addition, it was also a neutral metalo serine protease according tobiochemical tests that it was totaly inhibited by PMSF (Phenylmethanesulfonyl fluoride) and EDTA(Ethylenediaminetetraacetic acid). It showed optimum activity at pH of 8 and active in acidic buffer(up to pH of 4). All of metal ion in the form of chloride salt (2.5 mM) which were tested on theenzyme enhanced the enzyme activity but Li2+. Ca2+ion increased the activity and the stability ofenzyme against thermal. The enzyme also showed the stability against solvent. The protease LIIhad optimum temperature at 60oC without CaCl 2and 80 â 85oC with addition of 2.5 mM CaCl 2. TheK Mand V maxvalues for the purified protease LII were 27.2 mg/ml or 0.362 â 0.272 M for substrateHammersteinCasein (MM 75â100 kDa) and 261.1 Âµg/minute/ml, respectively.